Gastrointestinal symptoms in Fabry disease: everything is possible, including treatment. - Hoffmann, B; Keshav, S (2007)
UNLABELLED: Gastrointestinal symptoms in Fabry disease were first described independently by William Anderson and Johannes Fabry. Case reports and case series suggest that the whole gastrointestinal tract may be affected in patients with Fabry disease. The Fabry Outcome Survey (FOS) database supports these observations. The overall prevalence of gastrointestinal involvement reported in a study of 342 patients (271 adults; 71 children) enrolled in FOS was 52% (49.8% in adults, 60.8% in children). Abdominal pain was the most prevalent symptom. The median age at onset of gastrointestinal symptoms was 14 years, similar to the age at onset of acroparaesthesia. The prevalence of gastrointestinal symptoms was reduced in patients after receiving enzyme replacement therapy with agalsidase alfa for 12 and 24 months. There was no correlation between gastrointestinal symptoms and body mass index. CONCLUSION: Gastrointestinal symptoms in Fabry disease may have been underestimated. The FOS database supports previous reports of beneficial effects of enzyme replacement therapy on gastrointestinal symptoms in Fabry disease.